An overview of Indonesian doctors in combating COVID-19 - Yudanto, Ahmad V.; Ulfa, Maria; Wening, Dayu L.; Azuma, Momoyo (International Journal of Research in Medical Sciences, 2022)
Background: Indonesia’s COVID-19 pandemic is putting a strain on the ability of health systems around the world to adapt and maintain sustainable performance. Indonesia has had more than four million cases of the disease and more than 141 thousand deaths in Indonesia. The hospital, along with other healthcare facilities, contributes to providing comprehensive individual health care in outpatient, inpatient, and emergency settings. Changes in facilities for patient accommodation, and acquisition of personal protective equipment (PPE) are all going through substantial changes. As doctors and health workers continue to work on this case every day while out in the field, many of their colleagues become ill and some die as a result. The aim of the study was intended to provide an overview of the conditions faced by doctors in Indonesia in dealing with COVID-19. Methods: The researchers surveyed the situation of 270 Indonesian doctors and specialists working during the COVID-19 pandemic. The questionnaires adapted from the WHO risk assessment tool for healthcare workers were translated into Bahasa Indonesia and distributed from April 2021 to May 2021 using a retrospective study. Results: Most respondents were female (61.5%) with an average age of 27.7. Forty respondents (14.8%) had a history of COVID-19. Conclusions: Based on compliance with using PPE and compliance with washing hands, doctors in Indonesia had a low risk of contracting COVID-19 from the healthcare facility environment. Even so, a correlation was found between the history of COVID-19 and happiness at work.